Degradable RGD-Functionalized 3D-Printed Scaffold Promotes Osteogenesis. (September 2021) - Chang, P.-C.; Lin, Z.-J.; Luo, H.-T.; Tu, C.-C.; Tai, W.-C.; Chang, C.-H.; Chang, Y.-C.
To establish an ideal microenvironment for regenerating maxillofacial defects, recent research interests have concentrated on developing scaffolds with intricate configurations and manipulating the stiffness of extracellular matrix toward osteogenesis. Herein, we propose to infuse a degradable RGD-functionalized alginate matrix (RAM) with osteoid-like stiffness, as an artificial extracellular matrix, to a rigid 3D-printed hydroxyapatite scaffold for maxillofacial regeneration. The 3D-printed hydroxyapatite scaffold was produced by microextrusion technology and showed good dimensional stability with consistent microporous detail. RAM was crosslinked by calcium sulfate to manipulate the stiffness, and its degradation was accelerated by partial oxidation using sodium periodate. The results revealed that viability of bone marrow stem cells was significantly improved on the RAM and was promoted on the oxidized RAM. In addition, the migration and osteogenic differentiation of bone marrow stem cells were promoted on the RAM with osteoid-like stiffness, specifically on the oxidized RAM. The in vivo evidence revealed that nonoxidized RAM with osteoid-like stiffness upregulated osteogenic genes but prevented ingrowth of newly formed bone, leading to limited regeneration. Oxidized RAM with osteoid-like stiffness facilitated collagen synthesis, angiogenesis, and osteogenesis and induced robust bone formation, thereby significantly promoting maxillofacial regeneration. Overall, this study supported that in the stabilized microenvironment, oxidized RAM with osteoid-like stiffness offered requisite mechanical cues for osteogenesis and an appropriate degradation profile to facilitate bone formation. Combining the 3D-printed hydroxyapatite scaffold and oxidized RAM with osteoid-like stiffness may be an advantageous approach for maxillofacial regeneration.